2012
DOI: 10.1074/jbc.m111.304774
|View full text |Cite
|
Sign up to set email alerts
|

Association of Novel Domain in Active Site of Archaic Hyperthermophilic Maltogenic Amylase from Staphylothermus marinus

Abstract: Background: Maltogenic amylases that are known to date form dimers to perform hydrolysis. Results: The structure of maltogenic amylase from Staphylothermus showed a novel domain at the N terminus associated with the active site. Conclusion:Staphylothermus amylase has all of its substrate-binding structural components in a single monomer. Significance: This is the first report of the newly observed domain arrangement adopted by hyperthermophilic archaic maltogenic amylase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…Moreover, the crystal structure of maltogenic amylase from Staphylothermus marinus revealed that an N‐terminal extension forms the domain N′ that together with the A and C domains constitute the substrate‐binding pocket, distinguishing the archaeal enyzme from bacterial enzymes (T.‐Y. Jung et al., ). Domains N and N′ have the same functional roles in improving the characteristics of maltogenic amylases whether from mesophilic or thermophilic organisms.…”
Section: Specific Starch‐processing Enzymesmentioning
confidence: 99%
“…Moreover, the crystal structure of maltogenic amylase from Staphylothermus marinus revealed that an N‐terminal extension forms the domain N′ that together with the A and C domains constitute the substrate‐binding pocket, distinguishing the archaeal enyzme from bacterial enzymes (T.‐Y. Jung et al., ). Domains N and N′ have the same functional roles in improving the characteristics of maltogenic amylases whether from mesophilic or thermophilic organisms.…”
Section: Specific Starch‐processing Enzymesmentioning
confidence: 99%
“…This domain is also a member of the CBM48 (carbohydrate-binding module 48) family, the members of which include pullulanase, maltooligosyl trehalose synthase, starch branching enzyme, glycogen branching enzyme, glycogen debranching enzyme and isoamylase. In other microbial amylases, this region of the protein is referred to as the N 0domain and is involved in dimerization and the formation of a cap over the active-site cleft (Jung et al, 2012). However, gel-filtration experiments demonstrated that recombinant TK-PUL exists in a monomeric form.…”
Section: Structural Comparison With Homologuesmentioning
confidence: 99%
“…and maltogenic ␣-amylase (EC 3.2.1.133) (22,40), and neopullulanase (EC 3.2.1.135) (41,42), have been reported. A database search using the DALI server (43) revealed that CMMase shows a high structural similarity to GsNPL (Z-score, 53.3; RMSD, 1.5 Å for 435 C␣ atoms), TVAII (Z-score, 53.3; RMSD, 1.3 Å for 435 C␣ atoms), ThMAA (Z-score, 52.3; RMSD, 1.6 Å for 432 C␣ atoms), and a debranching enzyme from Nostoc punctiforme (NpDBE, Z-score, 46.6; RMSD, 2.0 Å for 420 C␣ atoms).…”
Section: Overall Structure Of Cmmasementioning
confidence: 99%